'Broadcast to mark Holocaust Memorial Day': Mass-mediated Holocaust commemoration on British television and radio. (October 2018) - Richardson, John E
This article examines the various programmes that British television and radio broadcast to mark Holocaust Memorial Day, between 2002 and 2016. Adopting a content analytic methodology, I quantified the broadcast schedules of 15 successive Holocaust Memorial Days, as recorded in archived copies of the Radio Times . My analysis reveals significant variations in mass-mediated Holocaust commemoration. Principally, I found a decrease in programming, despite a significant increase in the number of television channels; a tendency towards 'anniversarism' in the form and frequency of broadcast programmes; a stress on Auschwitz, as metonym of the Holocaust, and on survivors, children and music; and that commercial channels were significantly more likely to broadcast documentaries (and repeats) than the BBC's more varied and original outputs. These variations appear to be the result of three interlinked factors: First, a sense that the audience had grown weary of World War II commemoration, following saturation broadcasting of anniversaries in 2004 to 2005; changes in the management and programming priorities of key broadcasters, particularly the BBC; and that Holocaust Memorial Day has not yet become an established day for broadcasters in the nation's commemorative calendar.